Assessment of Antibodies Induced by Multivalent Transmission-Blocking Malaria Vaccines - Menon, Vinay; Kapulu, Melissa C.; Taylor, Iona; Jewell, Kerry; Li, Yuanyuan; Hill, Fergal; Long, Carole A.; Miura, Kazutoyo; Biswas, Sumi (Frontiers in Immunology, 2018)
A malaria transmission-blocking vaccine would be a critical tool in achieving malaria elimination and eradication. Using chimpanzee adenovirus serotype 63 and modified vaccinia virus Ankara viral vectored vaccines, we investigated whether incorporating two antigens into one vaccine would result in higher transmission-reducing activity than one antigen. We demonstrated that when Pfs25 was administered with other antigens Pfs28 or Pfs230C, either concurrently, as a mixed vaccine, or co-expressed as a dual-antigen vaccine, the antibody response in mice to each antigen was comparable to a mono-antigen vaccine, without immunological interference. However, we found that the transmission-reducing activity (functional activity) of dual-antigen vaccines was not additive. Dual-antigen vaccines generally only elicited similar transmission-reducing activity to mono-antigen vaccines, and in one instance had lower transmission-reducing activity. We found that despite the lack of immunological interference of dual-antigen vaccines, they are still not as effective at blocking malaria transmission as Pfs25-IMX313, the current leading candidate for viral vectored vaccines. Pfs25-IMX313 elicited similar quality antibodies to dual-antigen vaccines, but higher antibody titres.